2023
DOI: 10.3390/buildings13030637
|View full text |Cite
|
Sign up to set email alerts
|

Different Approach for the Structure Inclination Determination

Abstract: The current engineering and building pace has reached localities where vast civil projects were not considered. The changes of the intravillan area may cause some vacant historical localities to become a boundary or even a part of occupied area. The proximity of designed civil projects to historical structures may have great impact on their stability, and it is recommended or even legislatively set to monitor the possible changes in their shape or position. In case of protected structures, it is convenient to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Our open-access codes for both “checking” and “correcting” the stereochemistry are publicly accessible. 51 The above procedure might create a few overlaps between atoms; thus, we perform an additional energy minimization step followed by another short run, as illustrated in Figure 1 . Finally, the data for the analysis were collected from short MD simulations of a few (here 10) ns, labeled as runEQ, in which all monomers had the correct stereochemistry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our open-access codes for both “checking” and “correcting” the stereochemistry are publicly accessible. 51 The above procedure might create a few overlaps between atoms; thus, we perform an additional energy minimization step followed by another short run, as illustrated in Figure 1 . Finally, the data for the analysis were collected from short MD simulations of a few (here 10) ns, labeled as runEQ, in which all monomers had the correct stereochemistry.…”
Section: Resultsmentioning
confidence: 99%
“…The code for the development of the Deep Learning model and the computation of the dihedral angle distributions reported in the manuscript is uploaded in GitHub (see ref ( 57 )). Moreover, the codes developed and used for both “checking” and “correcting” the stereochemistry are publicly accessible in GitHub, together with the scripts for the calculation of the inner distances and radial distribution functions (see ref ( 51 )). We note that due to the magnitude of the trajectory files, only a small sample of the Copo100 system (100 frames) is available in GitHub (see ref ( 57 )); nevertheless, the rest of the data that support the findings of this study are available from the corresponding author upon request.…”
mentioning
confidence: 99%
“…LiDAR boasts an impressive accuracy, reaching up to 2-3 cm for horizontal coordinates (X, Y) and 3-5 cm for height (Z) when combined with GNSS data for georeferencing and IMU data for orientation [8]. It is important to note that such high-accuracy measurements are typically associated with large-scale surveys like topographic mapping [9].…”
Section: Introductionmentioning
confidence: 99%
“…The application of these methods has its pros and cons. However, a number of recent studies have shown that any of these methods can be successfully applied to monitor historic buildings [14][15][16][17][18][19][20][21][22][23][24][25]. In general, geospatial monitoring of engineering structures contains well-known stages, namely design, target setup, geodetic network creation, observations, data processing, and analysis.…”
Section: Introductionmentioning
confidence: 99%